Invitation to be the speaker for the symposium "Education and Research : Symposium on Computer Applications" - Hawkins, Richard (NIL, 1981)
Prof Diraja Ungku Aziz was invited to attend the symposium as the speaker by the PERNAS Trading SDN BHD and he accepted the offer